Environmental ethics and sustainability : a casebook for environmental professionals - Taback, H. J.; Ramanan, Ram (Boca Raton, FL : CRC Press, 2014)
'The environmental professional must be educated to be ethical, and more importantly, trained through frequent participatory workshops with real world scenarios to be able to make the right choices when faced with environmental dilemmas. This book serves as a reference and a resource casebook that will present current real world situations and provide perspectives to numerous environmental scenarios. It provides specific guidance as to what is ethical behavior, how to judge it, and provide the foundations of ethical behavior to guide the professional in facing and resolving ethical dilemmas. In addition, the authors present a framework for ethical decision making'--
Natural instincts and learned behavior -- Environmental ethics and public policy -- Environmental ethics and corporate governance -- Environmental ethics training for leaders and professionals -- Environmental dilemmas : on-the-job conflict situations -- Environmental dilemmas : judgment/decision situations.
Includes bibliographical references and index.
Keywords: Environmental ethics